TECHNIKI OBRAZOWANIANon-compaction of left and right ventricular myocardium – role of cardiac magnetic resonance imaging - Miszalski-Jamka, Karol; Rycaj, Jarosław; Głowacki, Jan; Chodór, Beata; Biełka, Agnieszka; Kłyś, Jan; Kwieciński, Radosław; Kalarus, Zbigniew (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Left ventricular non-compaction (LVNC) has gained growing awareness in the last two decades resulting in the exponential increase in number of diagnosed cases. This condition has already been reported as the third most frequent primary cardiomyopathy. It is characterized by the presence of non-compacted myocardial layer lining left ventricular cavity, although involvement of the right ventricle is not uncommon. LVNC could potentially lead to heart failure, ventricular arrhythmias and systemic embolic events, both in pediatric and adult populations. Echocardiography and cardiac magnetic resonance have been commonly used in patients suspected of LVNC. We present a case of a 12-year-old boy with non-compaction of left and right ventricular myocardium treated with orthotopic heart transplantation.